2016
DOI: 10.7554/elife.13426
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein IMP3 facilitates tumor immune escape by downregulating the stress-induced ligands ULPB2 and MICB

Abstract: Expression of the stress-induced ligands MICA, MICB and ULBP 1–6 are up-regulated as a cellular response to DNA damage, excessive proliferation or viral infection; thereby, they enable recognition and annihilation by immune cells that express the powerful activating receptor NKG2D. This receptor is present not exclusively, but primarily on NK cells. Knowledge about the regulatory mechanisms controlling ULBP expression is still vague. In this study, we report a direct interaction of the oncogenic RNA binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…We thus analyzed a relatively small but highly homogenous cohort of patients and corroborated clinical data with functional studies in patient-derived cell lines and/or IGF2BP3-silenced cells, in vitro and in vivo, to demonstrate that IGF2BP3 acts as a potent promoter of Ewing sarcoma malignancy. Several studies have described elevated expression of IGF2BP3 in human cancers, including osteosarcoma and leiomyosarcoma (38,45), and provided evidence that IGF2BP3 plays essential roles in the modulation of tumor cell fate, stemness, migration, metastasis, and immune escape (46). Studies recently performed in immortalized hMSCs have demonstrated IGF2BPs within a dicer-resistant set of genes with a pan-cancer relevance in tumor development (47).…”
Section: Discussionmentioning
confidence: 99%
“…We thus analyzed a relatively small but highly homogenous cohort of patients and corroborated clinical data with functional studies in patient-derived cell lines and/or IGF2BP3-silenced cells, in vitro and in vivo, to demonstrate that IGF2BP3 acts as a potent promoter of Ewing sarcoma malignancy. Several studies have described elevated expression of IGF2BP3 in human cancers, including osteosarcoma and leiomyosarcoma (38,45), and provided evidence that IGF2BP3 plays essential roles in the modulation of tumor cell fate, stemness, migration, metastasis, and immune escape (46). Studies recently performed in immortalized hMSCs have demonstrated IGF2BPs within a dicer-resistant set of genes with a pan-cancer relevance in tumor development (47).…”
Section: Discussionmentioning
confidence: 99%
“…By binding different mRNAs, IGF2BPs decide the fate of those mRNAs by controlling their localization, stability, and translation [40]. Many studies have reported the role of IGF2BPs in cell proliferation, cell invasion, tumorigenesis, and embryogenesis [40][41][42][43][44][45][46][47][48][49][50][51]. IGF2BPs have also been found in sheep trophoblast cells suggesting their role in rapid proliferation of these cells [52].…”
Section: Introductionmentioning
confidence: 99%
“…NK cells were purified and activated as previously described (47). For FACS-based determination of NK cell degranulation, 1 ϫ 10 5 NK cells were incubated without target cells or with 5 ϫ 10 4 SupT1 cells infected with Z29 for 12, 14, 16, or 22 h. For the blocking of activating receptors on NK cells, 0.25 g per well of antibody targeting NKG2D (R&D Systems) or NKp30 (Biolegend), or both antibodies simultaneously, was added prior to the experimental setup and incubated for 60 min on ice.…”
Section: Methodsmentioning
confidence: 99%